PERKEMBANGAN PENDIDIKAN ISLAM DI BRUNEI DARUSSALAM - Suddin Bani (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
Borneo Darussalam is one of the countries in the world claims itself as Islamic country that follows the Syafi’e school in Fiqh and Asy’ariyah in Theology. The history of Islam comes to Borneo Darussalam has some versions like another Asian countries. One version said that Islam came to Borneo in the 7 centuries and another version said that in the 13-14 centuries which was brought by Arabian Trade. Educational model in Borneo is the same in Singapore and Malaysia with the pattern A-7-3-2-2 by using Malay and English instruction with focusing on the priority of human’s morality to get religion and master technology. The government (Kingdom) has paid more attention to educational progress. The is shown to the educa-tional budget portion is too high and the position of education is very high to society’s view.